Effect of cyclodextrin complexation on phenylpropanoids’ solubility and antioxidant activity - Kfoury, Miriana; Landy, David; Auezova, Lizette; Greige-Gerges, Hélène; Fourmentin, Sophie (Beilstein Journal of Organic Chemistry, 2014)
The complexation abilities of five cyclodextrins (CDs) with seven phenylpropanoids (PPs) were evaluated by UV–visible spectroscopy, phase solubility studies and molecular modeling. Formation constants (Kf), complexation efficiency (CE), PP:CD molar ratio, increase in formulation bulk and complexation energy were assessed. All complexes exhibited a 1:1 stoichiometry but their stability was influenced by the nature and the position of the phenyl ring substituents. A relationship between the intrinsic solubility of guests (S0) and the solubilizing potential of CD was proposed. Molecular modeling was used to investigate the complementarities between host and guest. Finally, the antioxidant activity of encapsulated PPs was evaluated by scavenging of the stable DPPH radical.
Keywords: antioxidant activity; complexation efficiency; cyclodextrins; formation constant; phenylpropanoids; solubility

(untitled) - Ferrer, J.-L.; Austin, M. B.; Stewart, C., Jr; Noel, J. P. (Plant Physiol. Biochem., 2008)

(untitled) - Vogt, T. (Mol. Plant, 2010)

(untitled) - Lafay, S.; Gil-Izquierdo, A. (Phytochem. Rev., 2008)

(untitled) - Karakaya, S. (Crit. Rev. Food Sci. Nutr., 2004)

(untitled) - De Cássia da Silveira e Sá, R.; Andrade, L. N.; dos Reis Barreto de Oliveira, R.; de Sousa, D. P. (Molecules, 2014)

(untitled) - Korkina, L. G. (Cell. Mol. Biol., 2007)

(untitled) - El-Seedi, H. R.; El-Said, A. M. A.; Khalifa, S. A. M.; Göransson, U.; Bohlin, L.; Borg-Karlson, A.-K.; Verpoorte, R. (J. Agric. Food Chem., 2012)

(untitled) - Korkina, L.; Kostyuk, V.; de Luca, C.; Pastore, S. (Mini-Rev. Med. Chem., 2011)

(untitled) - Turek, C.; Stintzing, F. C. (Food Res. Int., 2012)

(untitled) - Pinho, E.; Grootveld, M.; Soares, G.; Henriques, M. (Carbohydr. Polym., 2014)

(untitled) - Ciobanu, A.; Landy, D.; Fourmentin, S. (Food Res. Int., 2013)

(untitled) - Carbal Marques, H. M. (Flavour Fragrance J., 2010)

(untitled) - Astray, G.; Gonzalez-Barreiro, C.; Mejuto, J. C.; Rial-Otero, R.; Simal-Gándara, J. (Food Hydrocolloids, 2009)

(untitled) - Szejtli, J. (Chem. Rev., 1998)

(untitled) - Armstrong, D. W.; Alak, A.; Bui, K.; Demond, W.; Ward, T.; Riehl, T. E.; Hinze, W. L. (J. Inclusion Phenom., 1984)

(untitled) - Fourmentin, S.; Ciobanu, A.; Landy, D.; Wenz, G. (Beilstein J. Org. Chem., 2013)

(untitled) - Ciobanu, A.; Mallard, I.; Landy, D.; Brabie, G.; Nistor, D.; Fourmentin, S. (Food Chem., 2013)

(untitled) - Loftsson, T.; Hreinsdóttir, D.; Másson, M. (Int. J. Pharm., 2005)

(untitled) - Loftsson, T.; Hreinsdóttir, D.; Másson, M. (J. Inclusion Phenom. Macrocyclic Chem., 2007)

(untitled) - Landy, D.; Fourmentin, S.; Salome, M.; Surpateanu, G. (J. Inclusion Phenom. Macrocyclic Chem., 2000)

(untitled) - Decock, G.; Fourmentin, S.; Surpateanu, G. G.; Landy, D.; Decock, P.; Surpateanu, G. (Supramol. Chem., 2006)

Log P

(untitled) - Kfoury, M.; Auezova, L.; Greige-Gerges, H.; Ruellan, S.; Fourmentin, S. (Food Chem., 2014)

(untitled) - Decock, G.; Landy, D.; Surpateanu, G.; Fourmentin, S. (J. Inclusion Phenom. Macrocyclic Chem., 2008)

(untitled) - Zhan, H.; Jiang, Z.-T.; Wang, Y.; Li, R.; Dong, T.-S. (Eur. Food Res. Technol., 2008)

(untitled) - Górnas, P.; Neunert, G.; Baczyński, K.; Polewski, K. (Food Chem., 2009)

(untitled) - Divakar, S.; Maheswaran, M. M. (J. Inclusion Phenom. Mol. Recognit. Chem., 1997)

(untitled) - Zhang, M.; Li, J.; Zhang, L.; Chao, J. (Spectrochim. Acta, Part A, 2009)

(untitled) - Anselmi, C.; Centini, M.; Maggiore, M.; Gaggelli, N.; Andreassi, M.; Buonocore, A.; Beretta, G.; Facino, R. M. (J. Pharm. Biomed. Anal., 2008)

(untitled) - Zhang, M.; Li, J.; Jia, W.; Chao, J.; Zhang, L. (Supramol. Chem., 2009)

(untitled) - Mathiron, D.; Marçon, F.; Dubaele, J.-M.; Cailleu, D.; Pilard, S.; Djedaïni-Pilard, F. (J. Pharm. Sci., 2013)

(untitled) - Kfoury, M.; Auezova, L.; Fourmentin, S.; Greige-Gerges, H. (J. Inclusion Phenom. Macrocyclic Chem., 2014)

(untitled) - Astray, G.; Mejuto, J. C.; Morales, J.; Rial-Otero, R.; Simal-Gándara, J. (Food Res. Int., 2010)

(untitled) - Demian, B. A. (Carbohydr. Res., 2000)

(untitled) - Hǎdǎrugǎ, D. I.; Hǎdǎrugǎ, N. G.; Bandur, G. N.; Isengard, H.-D. (Food Chem., 2012)

(untitled) - Stražišar, M.; Andrenšek, S.; Šmidovnik, A. (Food Chem., 2008)

(untitled) - Hill, L. E.; Gomes, C.; Taylor, T. M. (LWT–Food Sci. Technol., 2013)

(untitled) - Liang, H.; Yuan, Q.; Vriesekoop, F.; Lv, F. (Food Chem., 2012)

(untitled) - Wang, J.; Cao, Y.; Sun, B.; Wang, C. (Food Chem., 2011)

(untitled) - Badr-Eldin, S. M.; Elkheshen, S. A.; Ghorab, M. M. (Eur. J. Pharm. Biopharm., 2008)

(untitled) - Nuchuchua, O.; Saesoo, S.; Sramala, I.; Puttipipatkhachorn, S.; Soottitantawat, A.; Ruktanonchai, U. (Food Res. Int., 2009)

(untitled) - Brand-Williams, W.; Cuvelier, M. E.; Berset, C. (LWT–Food Sci. Technol., 1995)

(untitled) - Lucas-Abellán, C.; Mercader-Ros, M. T.; Zafrilla, M. P.; Gabaldón, J. A.; Núñez-Delicado, E. (Food Chem. Toxicol., 2011)

(untitled) - Zhao, M.; Wang, H.; Yang, B.; Tao, H. (Food Chem., 2010)

Advances in Analytical Chemistry and Instrumentation - Higuchi, T.; Connors, A. K. (Phase-Solubility Techniques, 1965)